An Investigation of the Use of IOT for Agricultural Output Monitoring and Control (International Journal of Food and Nutritional Sciences, 2022)
The notion of the Internet of Things (IoT) enables physical objects equipped with computational and sensory capabilities to communicate with one another and access online services. The goal behind the Internet of Things (IoT) was to link gadgets over the Internet and make it easier for users to obtain information. IoT has many potential uses, and one area where a lot of utilisation is anticipated in the future is agriculture. Presenting the Internet of Things concept as a foundation for farm production processes' monitoring and control systems was the goal of this endeavour. IoT devices are important, and their realisation is centred on the use of suitable sensors like those made by Arduino and readily available microcontroller platforms. In addition to collecting data for monitoring systems, autonomous sensor devices also assist in control by communicating with actuators through signals. Users of such an Internet of Things-based system can remotely monitor the industrial process and environmental conditions. With the help of this technology, users can cut costs, save input costs, and track the farm's production process